Algorithm of automatic control system of hydraulic excavator - R. Y. Sukharev; A. V. Starostin (Вестник СибАДИ)
There is presented the algorithm of automation of working process of hydraulic excavator in this article, that allows to dig trenches automatically and also the design scheme of the working equipment of hydraulic excavator in the working plane.